1980
DOI: 10.1147/rd.246.0695
|View full text |Cite
|
Sign up to set email alerts
|

The Experimental Compiling System

Abstract: The Experimental Compiling System (ECS) described here represents a new compiler construction methodology that uses a compiler base which can be augmented to create a compiler for any one of a wide class of source languages. The resulting compiler permits the user to select code quality ranging from highly optimized to interpretive. The investigation is concentrating on eo.vy expression and efficient implementation of language semantics; syntax analysis is ignored.The other unique feature of the schema is that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1981
1981
2004
2004

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Other groups subsequently made this sort of refinement to the methodology for their own purposes [11,12].…”
Section: Summary Of Experiencementioning
confidence: 99%
“…Other groups subsequently made this sort of refinement to the methodology for their own purposes [11,12].…”
Section: Summary Of Experiencementioning
confidence: 99%
“…Elegant, though not necessarily pragmatic or completely general, algorithms [78][79][80] now exist. A research project, the Experimental Compiling System [81][82][83], is investigating the use of interprocedural analysis [83,84] and optimization in a compiler building system. The basic ideas are to use procedures to express the semantics of the language being compiled, to deduce the characteristics of the language by analysis, to use procedure integration (in-Une expansion) to do code generation, and to optimize in order to customize and obtain good code.…”
Section: • Program Analysis and Optimizationmentioning
confidence: 99%
“…Ball showed a simple method for predicting the improvement possible with inline substitution, based on knowledge of the constant-valued parameters at a call site [4]. Allen, et al showed the potential for interprocedural improvement in their influential Experimental Compiling System [2]. Second, a growing body of evidence suggested that many call sites pass constant values as actual parameters, particularly to library routines [2,13].…”
Section: Introductionmentioning
confidence: 99%